Minimum Wage Compliance and Household Welfare: An Analysis of over 1500 Minimum Wages - Kashif Mansoor; Donal O'Neill (Institute of Labor Economics (IZA), 2020)
Minimum wages are increasingly being used in developing countries as a policy to combat exploitation of workers and raise living standards. However, in many developing countries there is a substantial difference between de jure and de facto regulation. We examine the consequences of imperfect compliance by looking at the heterogenous effects of minimum wages across compliance regimes in India from 1999-2011. We find noncompliance rates as high as 90% for some unskilled workers in India. We show that minimum wages have a positive effect on wages, without a corresponding effect on employment. As a result, household consumption increases following increases in the minimum wage; however, compliance matters. The beneficial pass-through of higher minimum wages to wages and consumption is significantly reduced in low compliance regimes. Our findings imply that labour market reforms have the potential to significantly improve workers' living standards in developing countries but only if accompanied by effective enforcement mechanisms.
Keywords: J38; O15; 330; minimum wage; compliance